Digital Technology to Support Sustainable Development Goals (SDGs): Literature Review - Ariansyah, Ariansyah; Prayogi, Saiful; Kurnia, Nova; Bilad, Muhammad Roil; Sutarto, Sutarto (Lensa: Jurnal Kependidikan Fisika, 2024)
Digital technology is a critical enabler in achieving Sustainable Development Goals (SDGs) by enhancing efficiency, transparency, and inclusivity across sectors such as education, health, economy, and the environment. This study employs a Narrative Literature Review (NLR) approach to explore the role of technologies like artificial intelligence (AI), the Internet of Things (IoT), and blockchain in advancing SDG targets. The research identifies opportunities for these technologies to improve service delivery, foster innovation, and mitigate challenges like unequal access, cybersecurity risks, and ethical concerns. The literature search covered journal articles, books, and reports from academic databases, focusing on keywords related to digital technologies and the SDGs. An analysis framework was applied to synthesize findings across diverse sectors. Results indicate that AI and IoT drive efficiency in education and healthcare, while blockchain enhances financial inclusivity and sustainable urban planning. However, disparities in digital access and ethical issues, such as data privacy, remain substantial obstacles. This review provides actionable insights for policymakers and stakeholders to leverage digital tools effectively for inclusive and sustainable development. Emphasizing multisectoral collaboration, the study underscores the importance of ethical frameworks and inclusive digital infrastructure to maximize technological benefits. These findings contribute to the broader understanding of digital technology’s integrative impact on sustainable development, offering strategic recommendations for future research and implementation.